(3GdCZGfjs - (3Ydj Hf GdMSjf Hf eMeO Hf CMeO Hf GdgjKe GdeQhGfj GdCehj GdbQTj, CHh GdaQL GdCUHgGfj, J (B356 (3g` s
(3ChdgG (B:s
(3jHOC GdehLhO efgG HCKfGA JQLeI YOi Hf RjO Hbhdg (B: (3Yf Hf MHjH Yfg hYf gTGe Hf GdcdjH Yf CHjg cGf SHH fRhd Gd YOi GdMjQI s
(3BNQgG (B:s
(3hCNQ GdehLhO efgG (B: (3JQLeI Pi GdCUHY dG JYLHf CeGe ef MOK aGdOgQ ZjQ fGaY GdMOKGf s
(3GdeNWhW bWYI ef ChGNQ GdLRA GdKGdK GdLRA GdQGHY Ydjg bQGAI SfI (B725s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B277 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B78 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B336s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B129s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
Keywords: (3GdCOHs